(untitled) (Modern American Journal of Biological and Environmental Sciences, 2025)
Atopic dermatitis (AD) is a chronic inflammatory disease characterized by impaired skin barrier and immune regulation. Vitamin D is considered a factor potentially influencing disease severity.